Hydrogen-rich syngas production of urea blended with biobutanol by a thermodynamic analysis. (13th September 2018) - Lin, Ke-Wei; Wu, Horng-Wen
Abstract: Both biobutanol and urea are the environment-friendly hydrogen carrier. This study is to compare hydrogen production between steam reforming of biobutanol and autothermal reforming of biobutanol feed using pure steam and vaporization of aqueous urea (VAU) by a thermodynamic analysis. Hydrogen-rich syngas production, carbon formation, thermal neutral temperature (TNT), and hydrogen production cost are analyzed in both steam reforming and autothermal reforming. The results show that hydrogen-rich syngas production with the use of VAU is higher than that with pure steam not only in steam reforming but also in autothermal reforming. When the VAU/butanol molar ratio is 8, and the O2 /butanol molar ratio equals 3, the reforming efficiency reaches up to 81.42%. At the same condition, the hydrogen production cost is lower than that without blending urea. Therefore, using VAU to replace pure steam in biobutanol reforming leads to benefits of increasing the hydrogen-rich syngas yield and lowering cost. Highlights: We analyze steam and autothermal reforming of biobutanol blended with aqueous urea. Blending aqueous urea replace steam raises syngas yield and reforming efficiency. Blending biobutanol with aqueous urea reduces thermal neutral temperature. Reforming efficiency of biobutanol blended with aqueous urea is up to 81.42%. Cost of hydrogen production with aqueous urea is lower than without aqueous urea.